2021
DOI: 10.1200/jco.2021.39.15_suppl.10563
|View full text |Cite
|
Sign up to set email alerts
|

Young-onset colorectal cancer: A call for action.

Abstract: 10563 Background: Young-onset colorectal cancer (YOCR) is defined as diagnosis below the age of 50. Over the past decades, the incidence of YOCRC has increased at an alarming rate, but causes and pathogenesis still remain unknown. Early detection of colorectal cancer (CRC) has demonstrated to improve survival. Despite these facts, adults < 50 years old are not yet included in screening programs and YOCRC is not well characterized. We aimed to characterize the clinical and molecular characteristics of YOCRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies comparing outcomes between eo-CRC and ro-CRC have reported conflicting results. Some suggested worse survival among early-onset CRC patients, while the majority reported similar prognosis [9,10,[20][21][22][23]]. An analysis of the National Cancer Database reports that the impact of age as a positive prognostic vanishes with rising tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing outcomes between eo-CRC and ro-CRC have reported conflicting results. Some suggested worse survival among early-onset CRC patients, while the majority reported similar prognosis [9,10,[20][21][22][23]]. An analysis of the National Cancer Database reports that the impact of age as a positive prognostic vanishes with rising tumor stage.…”
Section: Discussionmentioning
confidence: 99%